Centro de artes y oficios para la mujer víctima de violencia de género del Municipio de Bucaramanga. - Beltrán Meza, Jasón Ernesto (Universidad Antonio Nariño, 2022)
The initiative of a design proposal as an architectural solution for a care center for women victims of gender violence in the municipality of Bucaramanga, seeks the insertion of women who today are physically and psychologically violated, and for women who want undertake and seek economic independence.